Investigation of The Effects of Temperature on Physical, Mechanical And Electrical Conductivity Properties in AISI 310S Austenitic Stainless Steel - Özlü Torun, Handan; Taşdemir, Vedat; Kerli, Süleyman (Physics and Chemistry of Solid State, 2021)
In our study, annealing was done to AISI 310S stainless steel at 800 °C. The effects of these annealing on structural, morphological, mechanical and electrical conductivities were investigated. From XRD results, it has been observed that the material is austenite and cubic in nature. SEM analysis has shown that the surface of AISI 310S steel changes with temperature. The tensile test of the material was made and it was observed that the tensile strength of the material decreased with the effect of temperature. In addition, the conductivity behavior of AISI 310S steel was measured with four probe technique depending on heat treatment. As a result of the measurements, it was observed that the resistance value increased and the conductivity value decreased in the heat treated material.